Cultural significance as a concept for the delimitation of historic centers (2021)
According to Colombian legislation and as a National Asset of Cultural Interest, the historic center of the municipality of Villa de Leyva required the formulation of a Special Management and Protection Plan (SMPP), which is a territorial management instrument for the preservation of cultural heritage. The elaboration of this SMPP is based on the reflections and conceptualization contained in various expert pronouncements, which led to the proposal of delimitation of the affected area and the zone of influence; to this end, the research was based on historical documents, blueprints, aerial photographs, field trips, photographic research, interviews and surveys, previous studies and working groups with the municipal administration and with local groups and stakeholders. The analysis of the information made it possible to define a set of criteria and values (which go beyond of what is established in the national regulations) that constitute the cultural significance and which, at the same time, are the basis for the delimitation of the historic center. Beyond establishing a perimeter or a dividing line that defines an inside or an outside of the affected area and the required zone of influence, we propose, as the basis of the delimitation, the axes and spaces of cultural significance, whose characteristics express not only the heritage values of the physical spaces of this place, but also the associated cultural practices. We consider this to be an innovative proposal for this type of technical document for the public management of cultural heritage.